Factors affecting cognitive frailty improvement and progression in Taiwanese older adults - Lalu Suprawesta; Sy-Jou Chen; Hui-Yu Liang; Hei-Fen Hwang; Wen-Yu Yu; Mau-Roung Lin (BMC Geriatrics, 2024)
Abstract Background Knowledge of predictors of cognitive frailty (CF) trajectories is required to develop preventive strategies to delay or reverse the progression from CF to dementia and other adverse outcomes. This 2-year prospective study aimed to investigate factors affecting the progression and improvement of CF in older Taiwanese adults. Methods In total, 832 community-dwelling people aged ≥ 65 years were eligible. Fried’s five frailty criteria were used to measure prefrailty and frailty, while cognitive performance was assessed by the Clinical Dementia Rating and Mini-Mental State Examination. Each component of reversible CF and potentially reversible CF was assigned a score, with a total score ranging 0 to 5 points. Two annual follow-up CF assessments were conducted. The group-based trajectory model was applied to identify latent CF trajectory groups, and a multinomial logistic regression was used to examine relationships of explanatory variables with CF trajectories. Results According to data on 482 subjects who completed the two annual follow-ups, three CF trajectories of robust, improvement, and progression were identified. After adjusting for the baseline CF state, CF progression was significantly associated with an older age (odds ratio [OR] = 1.08; 95% confidence interval [CI], 1.02 ~ 1.14), a lower Tinetti balance score (OR = 0.72; 95% CI, 0.54 ~ 0.96), a slower gait (OR = 0.98; 95% CI, 0.97 ~ 0.99), and four or more comorbidities (OR = 2.65; 95% CI, 1.19 ~ 5.90), while CF improvement was not significantly associated with any variable except the baseline CF state. In contrast, without adjusting for the baseline CF state, CF progression was significantly associated with an older age, female sex, balance scores, gait velocity, regular exercise, the number of comorbidities, and depression, while CF improvement was significantly associated with female sex, balance scores, and the number of comorbidities. Conclusions The baseline CF state, an older age, poorer balance, slower gait, and a high number of comorbidities may contribute to CF progression, while the baseline CF state may account for associations of engaging in regular exercise and depression with CF development.